Hydrogenated Graphene Improves Neuronal Network Maturation and Excitatory Transmission. Issue 1 (4th January 2021) - Moschetta, Matteo; Lee, Jong‐Young; Rodrigues, João; Podestà, Alice; Varvicchio, Omar; Son, Jangyup; Lee, Yangjin; Kim, Kwanpyo; Lee, Gwan‐Hyoung; Benfenati, Fabio; Bramini, Mattia; Capasso, Andrea
Abstract: Graphene is regarded as a viable bio‐interface for neuroscience due to its biocompatibility and electrical conductivity, which would contribute to efficient neuronal network signaling. Here, monolayer graphene grown via chemical vapor deposition is treated with remote hydrogen plasma to demonstrate that hydrogenated graphene (HGr) fosters improved cell‐to‐cell communication with respect to pristine graphene in primary cortical neurons. When transferred to polyethylene terephthalate, HGr exhibits higher wettability than graphene (water contact angle of 83.7° vs 40.7°), while preserving electrical conductivity (≈3 kΩ □ ‐1 ). A rich and mature network is observed to develop onto HGr. The intrinsic excitability and firing properties of neurons plated onto HGr appears unaltered, while the basic passive and active membrane properties are fully preserved. The formation of excitatory synaptic connections increases in HGr with respect to pristine graphene, leading to a doubled miniature excitatory postsynaptic current frequency. This study supports the use of hydrogenation for tailoring graphene into an improved neuronal interface, indicating that wettability, more than electrical conductivity, is the key parameter to be controlled. The use of HGr can bring about a deeper understanding of neuronal behavior on artificial bio‐interfaces and provide new insight for graphene‐based biomedical applications. Abstract : Chemical vapor deposited graphene treated with remote hydrogen plasma fosters cell‐to‐cell communication in primary cortical neurons. Transferred to polyethylene terephthalate, hydrogenated graphene (HGr) exhibits a higher water contact angle than graphene (83.7° vs 40.7°), while preserving electrical conductivity (≈3 kΩ □ ‐1 ). Onto HGr, a rich and mature neuronal network develops with improved neuronal signaling, highlighted by a doubled miniature post‐synaptic excitatory frequency.